Induced resistance in tomato by SAR activators during predisposing salinity stress - Pye, Matthew F.; Hakuno, Fumiaki; MacDonald, James D.; Bostock, Richard M. (Frontiers in Plant Science, 2013)
Plant activators are chemicals that induce disease resistance. The phytohormone salicylic acid (SA) is a crucial signal for systemic acquired resistance (SAR), and SA-mediated resistance is a target of several commercial plant activators, including Actigard (1,2,3-benzothiadiazole-7-thiocarboxylic acid-s-methyl-ester, BTH) and Tiadinil (N-(3-chloro-4-methylphenyl)-4-methyl-1,2,3-thiadiazole-5-carboxamide, TDL). BTH and TDL were examined for their impact on abscisic acid (ABA)-mediated, salt-induced disease predisposition in tomato seedlings. A brief episode of salt stress to roots significantly increased the severity of disease caused by Pseudomonas syringae pv. tomato (Pst) and Phytophthora capsici relative to non-stressed plants. Root treatment with TDL induced resistance to Pst in leaves and provided protection in both non-stressed and salt-stressed seedlings in WT and highly susceptible NahG plants. Non-stressed and salt-stressed ABA-deficient sitiens mutants were highly resistant to Pst. Neither TDL nor BTH induced resistance to root infection by P. capsici, nor did they moderate the salt-induced increment in disease severity. Root treatment with these plant activators increased the levels of ABA in roots and shoots similar to levels observed in salt-stressed plants. The results indicate that SAR activators can protect tomato plants from bacterial speck disease under predisposing salt stress, and suggest that some SA-mediated defense responses function sufficiently in plants with elevated levels of ABA.